The Beneficial Effects of Beta Blockers on the Long-Term Prognosis of Patients With Premature Atrial Complexes - Huang, Ting-Chun; Lee, Po-Tseng; Huang, Mu-Shiang; Chiu, Pin-Hsuan; Su, Pei-Fang; Liu, Ping-Yen (Frontiers in Cardiovascular Medicine, 2022)
Aims Premature atrial complexes (PACs) have been reported to increase the risk of adverse cardiovascular outcomes. Beta blockers at low dosages may help to reduce PAC symptoms, but it is unclear whether they can improve long-term outcomes. Methods Patients enrolled from a Holter cohort in a medical referral center were stratified into high-burden (≥100 beats/24 h) and low-burden (<100 beats/24 h) sub-cohorts, and propensity score matching between treatment groups and non-treatment groups was conducted for each sub-cohort. Results In the high-burden sub-cohort, after propensity score matching, the treatment group and non-treatment group respectively had 208 and 832 patients. The treatment group had significantly lower mortality rates than the non-treatment group [hazard ratio (HR) = 0.521, 95% confidence interval (CI) = 0.294–0.923, p = 0.025], but there was no difference in new stroke (HR = 0.830, 95% CI = 0.341–2.020, p = 0.681), and new atrial fibrillation (HR = 1.410, 95% CI = 0.867–2.292, p = 0.167) events. In the low-burden sub-cohort, after propensity score matching, there were 614 patients in the treatment group and 1,228 patients in the non-treatment group. Compared to the non-treatment group, up to 40% risk reduction in mortality was found in the treatment group (HR = 0.601, 95% CI = 0.396–0.913, p = 0.017), but no differences in new stroke (HR =0.969, 95% CI = 0.562–1.670, p = 0.910) or atrial fibrillation (HR = 1.074, 95% CI = 0.619–1.863, p = 0.800) were found. Conclusions Beta blockers consistently decreased long-term mortality in high-burden and low-burden patients. Interestingly, this effect was not achieved through reduction of new-onset stroke or AF, and further research is warranted.